Claiming a corner at work: Measuring employee territoriality in their workspaces - Brown, Graham (Academic Press, 2009)
Territoriality is an emerging concept of importance in organizations. Unfortunately, there does not exist currently a valid measure of territoriality with which to conduct research on territoriality in organizations. I developed a theoretically driven four-factor measure of territoriality. Six hundred and sixty-three people working in office settings completed an online survey about their territorial behaviors. Using confirmatory factor analysis I found that the four-factor structure had acceptable fit. I also found preliminary evidence of construct validity. Collectively, the results support the validity of the measure, thus providing an instrument for studying territoriality in organizations. I then discuss specific implications of this measure for both research and practise. © 2008 Elsevier Ltd. All rights reserved.